Prognostic impact of cardiac surgery in left-sided infective endocarditis according to risk profile. Issue 24 (11th September 2021) - Garcia Granja, Pablo Elpidio; Lopez, Javier; Vilacosta, Isidre; Saéz, Carmen; Cabezón, Gonzalo; Olmos, Carmen; Jerónimo, Adrián; Pérez, Javier B; De Stefano, Salvatore; Maroto, Luis; Carnero, Manuel; Monguio, Emilio; et al.
Abstract : Objective: To evaluate the prognostic impact of urgent cardiac surgery on the prognosis of left-sided infective endocarditis (LSIE) and its relationship to the basal risk of the patient and to the surgical indication. Methods: 605 patients with LSIE and formal surgical indication were consecutively recruited between 2000 and 2020 among three tertiary centres: 405 underwent surgery during the active phase of the disease and 200 did not despite having indication. The prognostic impact of urgent surgery was evaluated by multivariable analysis and propensity score analysis. We studied the benefit of surgery according to baseline mortality risk defined by the ENDOVAL score and according to surgical indication. Results: Surgery is an independent predictor of survival in LSIE with surgical indication both by multivariable analysis (OR 0.260, 95% CI 0.162 to 0.416) and propensity score (mortality 40% vs 66%, p<0.001). Its greatest prognostic benefit is seen in patients at highest risk (predicted mortality 80%–100%: OR 0.08, 95% CI 0.021 to 0.299). The benefit of surgery is especially remarkable for uncontrolled infection indication (OR 0.385, 95% CI 0.194 to 0.765), even in combination with heart failure (OR 0.220, 95% CI 0.077 to 0.632). Conclusions: Surgery during active LSIE seems to significantly reduce in-hospital mortality. The higher the risk, the higher the improvement in outcome.